My experiences with breathing problems during elite Judo competition - Rubinstein, M. (British Journal of Sports Medicine, 2022)
Breathing problems can potentially ruin all type of sports careers, so as an athlete it is important to discuss these issues early with your clinicians so they can help you get to the root of the problem.